Australasian Pleistocene cometary impact and its effects in Thailand - Bunopas, Sangad; Kieren Howard, with contributions from (Thai Geoscience Journal, 2021)
Tektites are silica-rich glasses distributed in 4 strewn fields around 3 definite impact craters in the USA, Ghana and Germany and the Australasian strewn field around possibly one or more craters in Indochina. The distribution, morphology, size, mineralogy, geochemistry and contained gases of Australasian tektites confirms their terrestrial origin from a sandstone target rock of approximately Jurassic age and an impact site or sites within or offshore Indochina. The Indochina impact is dated at about 788 ka. Layered tektites are known from a more limited area and probably are proximal to the impact crater or craters. The largest layered tektites weigh up to 24 kg and come from Ubon Ratchathani Province in NE Thailand or perhaps from neighbouring Laos. Dumbbell, spherical, teardrop and disc shaped splash-form tektites are found across SE Asia and southern China. Aero-ablated tektites (australite buttons) extend to the Indian Ocean and Australia and microtektites are found in Antarctica and in deep-sea cores from the Indian Ocean and the marginal seas of the western Pacific. In many deep-sea cores, microtektites occur just below the Matuyama-Brunhes magnetic reversal dated at about 772.9 ± 5.4 ka. and occur with high pressure minerals such as coesite. Coesite and reidite along with silt-size detrital minerals within layered tektites are conclusive evidence of an impact origin. The abundance and distribution of iridum and microtektites in ocean cores has led several authors to calculations of a single crater size of between 15 km and >120 km with a most likely diameter of about 40 + km. Both layered tektites and splash-form tektites occur at the junction of laterite and a loess-like sand or rarely within the loess, across much of SE Asia and this stratigraphic relationship is especially clear on the Khorat Plateau in NE Thailand. The widespread loess is different to typical Chinese loess, is palaeoclimatically anomalous and is considered herein as ‘catastroloess’ – the result of the 788 ka impact event. Unreworked, tektites, including one very fragile hollow sphere, are also found in fluvial sands dated by thermoluminescence as 748 ka in Nakhon Ratchasima (Khorat) Province along with large, unusually very abundant charcoalified and partially charcoalified trees and smaller plant matter such as bamboo. This section of the sandpits along the palaeo-Mun River contains Pleistocene vertebrates in the upper sections and Miocene vertebrates below the tektite horizon. The tektite horizon occurs close to the Matuyama-Brunhes magnetic reversal. The sandpits are argued to contain globally unique evidence of a large extraterrestrial impact event. Impact craters and abundant impact glasses at the Zhamanshin crater in Kazakhstan (c. 920-650 ka) and at the Darwin Crater in Tasmania, Australia (816 ± 7 ka) are argued to be contemporaneous with the Australasian strewn field and the result of a comet travelling southeastwards and disintegrating, creating catastrophic impacts first in Kazakhstan, then in Indochina and finally in Tasmania. This hypothetical trail of impacts is comparable to the disintegration and multiple impacts of the Shoemaker-Levy comet fragments into Jupiter’s atmosphere in 1994. These multiple impacts on Earth would have had profound effects on faunas, climate and sedimentation along the comet’s path including on our immediate ancestor Homo erectus in China, in Java and possibly in Lampang and Nan in Thailand. More evidence of impact in Thailand may be present near Nan and Phrae in northern Thailand and at Sra Kaeo in eastern Thailand where sao din or earth pillars are eroded ‘catastroloess’ and at Bo Phloi in western Thailand where sand-pits contain abundant charcoalified logs. Large trees within river terrace gravels at Khorat (with a tektite) and at Tak in NW Thailand may also be due to the impact. Other proposed impact effects on probable Miocene fish mortality in Phetchabun, MiocenePleistocene mammal mortality in Australia, probably Holocene shell-beds around Bangkok and the Inthanon Uplift in northern Thailand should be considered but are more speculative.